The effects of student loan debt on financial worry - Gallardo, Juan E. (Kansas State University, 2023)
With the costs of higher education increasing, the need to search for alternative ways to fund these expenses has also increased. While grants, scholarships, personal savings, and financial assistance from parents, may be effective for some, this is not the case for all students as some are inclined to use student loans to fund their higher education journey. Though student loan debt is an issue globally, Americans in particular face an enormous student loan deficit—$1.5 trillion, twice what it was a decade ago (Casey, 2020). The problem is not that student loans exist, as they provide an avenue to complete a degree, the issue arises when someone cannot pay back these loans because they are stretched very thin financially when the payment period begins. This can cause individuals to worry about the future of their finances. Drawing from student loan debt and worry research, this study highlights the degree to which student loan debt influences financial worry and seeks to explain the magnitude (i.e., to what degree student loans are tied to worry) and the mechanism by which student loans influence financial worry. (i.e., how does this happen). For the purpose of this study, financial worry was conceptualized as repetitive negative thoughts about uncertain future events, and a scale was created that encompasses retirement worry, personal finance anxiety, and physical and emotional financial stress. The study is guided by the Tallis and Eynseck model of worry. The model states that worry is activated when the severity of a perceived threat exceeds the estimated coping resources. Once a stressor is perceived, that stressor is then evaluated based on its severity. In this research, the stressor is student loan debt. Depending on the severity of the stressor, that stressor then influences an individual’s perception of how threatening it is. These threats can be objective or subjective and can also influence financial worry. The study used the 2018 National Financial Capability Study (NFCS) dataset. To take the model to data, student loans were categorized as two variables, student loans that are not delinquent and delinquent student loans. Results were then compared to individuals who do not have any student loans. Analyses showed a direct positive relationship between student loan debt delinquency and student loan debt non-delinquency to both objective and subjective financial threats. The magnitude of the student loan delinquency effect was greater than that of non-delinquency on both subjective and objective stressors. Furthermore, subjective and objective financial stress were both positively associated with financial worry. When objective and subjective threat stressors were included, student loan delinquency and student loan non-delinquency were not significant predictors of financial worry at the .05 level. Results from the present study contribute to the literature on financial worry, financial stress, and student loan debt. Results also provide the foundation for understanding the influence of student loan debt on financial worry as well as understanding the influence of coping mechanisms to decrease such financial worry. The results of the present study should be of interest to policymakers, financial and mental health professionals, and students who may rely on debt for attending an institution of higher education.
Keywords: Financial worry; Student loan debt; Financial stress; Coping mechanisms